Preparation of Metal Mold For Production Of Microwave Flask - Nadira A Hatim; Radhwan H Hasan (University of Mosul, College of Dentistry, 2009)
Aims: To design and prepare a metal mold used for production of Fiber Reinforced plastic flask (FRP)suitable for curing of acrylic resin by microwave irradiation, and investigate the effect of the following variableson the shear bond strength (SBS) of acrylic teeth to acrylic denture base material: A-curing techniques(water bath and microwave). B-surface treatment with monomer. C-cross - linking of the tooth resinby using the new microwave flask. Materials and methods: The FRP flask is not available in our countryso as a special design of metal mold was prepared for this study. Inner dimensions were determined accordingto standard Ash metal flask. A microwave flask was fabricated from unsaturated polyester resin reinforcedwith glass fibers, nuts and screws was fabricated from Teflon material which are available in ourcountry. One hundred sixty samples of five different brands of acrylic teeth were divided into four groups{untreated and treated (with monomer )groups each of these were cured by water bath or microwave techniques}.The bond strength between acrylic tooth and denture base resin was measured in shear mode byusing unconfined compression machine, the SBS in MPa was calculated. Analysis of variance (ANOVA)and Duncan's multiple range test were used for statistical analysis. Results: There was a significant differencesin bond strength of acrylic denture base to different tooth materials by using FRP flask in relation toAsh metal flask at (P < 0.001). Conclusions: SBS of acrylic teeth improved by monomer surface treatmentfor 180 seconds to microwave cured resin by new prepared flask (FRP) was significantly higher than that ofwater - bath cured resin, and cross - linked acrylic teeth showed lowest SBS compared to other type ofacrylic teeth.